2023
DOI: 10.3389/fgene.2023.1061002
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite instability-related prognostic risk score (MSI-pRS) defines a subset of lung squamous cell carcinoma (LUSC) patients with genomic instability and poor clinical outcome

Abstract: Background: Lung squamous cell carcinoma (LUSC) shares less typical onco-drivers and target resistance, but a high overall mutation rate and marked genomic complexity. Mismatch repair (MMR) deficiency leads to microsatellite instability (MSI) and genomic instability. MSI is not an ideal option for prognosis of LUSC, whereas its function deserves exploration.Method: MSI status was classified by MMR proteins using unsupervised clustering in the TCGA–LUSC dataset. The MSI score of each sample was determined by ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…The study by Jonathan demonstrated that MSI may be associated with the presence of new immunogenic epitopes to more precisely guide immunotherapy ( Dudley et al, 2016 ). A previous study showed that LUSC patients with high MSI tend to have improved OS ( Hu et al, 2023 ). In our study, MCM3 expression was positively related to MSI level in STAD, KIRC, LUAD and LUSC.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Jonathan demonstrated that MSI may be associated with the presence of new immunogenic epitopes to more precisely guide immunotherapy ( Dudley et al, 2016 ). A previous study showed that LUSC patients with high MSI tend to have improved OS ( Hu et al, 2023 ). In our study, MCM3 expression was positively related to MSI level in STAD, KIRC, LUAD and LUSC.…”
Section: Discussionmentioning
confidence: 99%